基于齿轮箱整体模型的齿轮有限元接触分析 - 尚振国; 王华 (Jixie Chuandong, 2012)
The calculation method of the whole gearbox deformation is proposed by the application of superposition principle,including the gear box case body,bearing,shaft and gears.The flexibility matrix of the gear box case body is generated by using the rigid coupling function in ANSYS.Accordingly,the deformation of the gear box case body is gained by solving the relationship equation of the flexibility matrix,load vector and deformation vector.Taking a wind turbine speed increasing gear box as an example,the influence of the whole gearbox deformation on the reaction force of the supporting points and the bending stress is analyzed.